Conjugate hemisphere ionospheric response to the St. Patrick's Day storms of 2013 and 2015 in the 100°E longitude sector. Issue 11 (11th November 2016) - Kalita, Bitap Raj; Hazarika, Rumajyoti; Kakoti, Geetashree; Bhuyan, P. K.; Chakrabarty, D.; Seemala, G. K.; Wang, K.; Sharma, S.; Yokoyama, T.; Supnithi, P.; Komolmis, T.; Yatini, C. Y.; et al.
Abstract: The effects of the St. Patrick's Day geomagnetic storms of 2013 and 2015 in the equatorial and low‐latitude regions of both hemispheres in the 100°E longitude sector is investigated and compared with the response in the Indian sector at 77°E. The data from a chain of ionosondes and GPS/Global Navigation Satellite Systems receivers at magnetic conjugate locations in the 100°E sector have been used. The perturbation in the equatorial zonal electric field due to the prompt penetration of the magnetospheric convective under shielded electric field and the over shielding electric field gives rise to rapid fluctuations in the F 2 layer parameters. The direction of IMF Bz and disturbance electric field perturbations in the sunset/sunrise period is found to play a crucial role in deciding the extent of prereversal enhancement which in turn affect the irregularity formation (equatorial spread F ) in the equatorial region. The northward (southward) IMF Bz in the sunset period inhibited (supported) the irregularity formation in 2015 (2013) in the 100°E sector. Large height increase ( hm F 2 ) during sunrise produced short‐duration irregularities during both the storms. The westward disturbance electric field on 18 March inhibited the equatorial ionization anomaly causing negative (positive) storm effect in low latitude (equatorial) region. The negative effect was amplified in low midlatitude by disturbed thermospheric composition which produced severe density/total electron content depletion. The longitudinal and hemispheric asymmetry of storm response is observed and attributed to electrodynamic and thermospheric differences. Key Points: Differential ionospheric response between two equinoctial storms is investigated in the 100°E meridian with conjugate hemisphere data Contribution of the electrodynamics and thermospheric composition change to severe negative storm effect is assessed Generation of equatorial irregularities is observed in the sunrise period due to disturbance electric field